Renovation of the post-soviet housing estates in the context of pandemic challenges on the example of Novi Budynky in Kharkiv - Antonenko, Nadiia; Didenko, Kateryna (Landscape Architecture and Art, 2025)
This study raises the question of revising the usual ideas about the renovation of post-Soviet housing. The new urban movements that have become popular in the context of the COVID-19 pandemic, namely, the concept of the "15-minute city" are taking into account. The purpose of this publication is to identify possible methodological and theoretical shifts in research approaches in dealing with the transformation of post-Soviet residential areas in connection with the active introduction of new concepts of chrono-urbanism, such as the "15-minute city". In order to achieve the goal, a systematic logical and analytical approachs were used to identify the concept of a 15-minute city that is relevant today as one of those that can be used for the renovation and revitalisation of post-Soviet residential areas. The study uses a comparative method, includes a study of literary and documentary sources. The method of information systematisation was also used to summarise the research results. As a site for field research, the Novi Budynky housing estate in Kharkiv was chosen, on the example of which a historical study was carried out. It was analyzed how this housing estate corresponded to contemporary ideas about normal socio-cultural and living conditions, its new functional content, and also analyzed the possible whether (from the point of view of the formed morphology and the established service system) to introduce the concept of "15-minute city". The first steps that can be taken to get closer to the implementation of this concept were formulated, and practical and methodological problems of its implementation into the reality of post-Soviet cities, in the form in which it was theoretically developed, were identified.